ESTIMATION OF PROTEIN CONCENTRATION IN FOOD BY TOTAL NITROGEN AND AMINO ACID ANALYSES - Sumarno .; Sri Noegrohati; Narsito .; Iip Izul Falah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Since protein is the principal constituent of biological organs, a continuous supply is needed in food for growth and repair. Protein quality in food is determined by its assortment of amino acids, whether it is essentially needed or not. The aim of this study is to develop an accurate and precise simple method of protein estimation for food and feed. The validity of simple protein estimation by multiplying the N-total concentration with a constant factor: of 6.25, should be clarified. Protein could be estimated more specifically by summing up the determined amino acids. In this study, the amino acids of some substantially high protein food were analysed by HPLC-ninhydrin, HPLC-o-phthalaldehyde, and HPLC-dansyl techniques, by gas chromatograph after derivation with TFA-butanol, and by formol titration. Method based on HPLC-ninhydrin techniques shows significant correlation (r=0-9992) with its amino acids content and N-total content. The protein as amino acids - N-total conversion factor obtained was 6.95 for N-total content less than 15.5%, and 8.59 for N-total content higher than 15.5%.Key words: food, protein and analytical methods